Design of ultrasonic probes for medical diagnostics - ŁYPACEWICZ, G.; DURIASZ, E. (Archives of Acoustics, 1990)
The Mason's equivalent circuit of the piezoelectric transducer is modified in order to investigate separately the influence of parameters of piezoelectric material as well as electrical and acoustical elements applied in the ultrasonic probe. All values transfered to the mechanical side of the electromechanical transformer let us introduce the relative values both electrical and acoustical parameters. The mechanical and dielectric losses of the transducer are taken into consideration.The influence of various parameters of the probe on input admittance and reflected from an ideal reflector pulses is shown.